Comparative Microbiome Analysis of a Fusarium Wilt Suppressive Soil and a Fusarium Wilt Conducive Soil From the Châteaurenard Region - Siegel-Hertz, Katarzyna; Edel-Hermann, Véronique; Chapelle, Emilie; Terrat, Sébastien; Raaijmakers, Jos M.; Steinberg, Christian (Frontiers in Microbiology, 2018)
Disease-suppressive soils are soils in which specific soil-borne plant pathogens cause only limited disease although the pathogen and susceptible host plants are both present. Suppressiveness is in most cases of microbial origin. We conducted a comparative metabarcoding analysis of the taxonomic diversity of fungal and bacterial communities from suppressive or non-suppressive (conducive) soils as regards Fusarium wilts sampled from the Châteaurenard region (France). Bioassays confirmed that disease incidence was significantly lower in the suppressive soil than in the conducive soil. Furthermore, we succeeded in partly transferring Fusarium wilt-suppressiveness to the conducive soil by mixing 10% (w/w) of the suppressive soil into the conducive soil. Fungal diversity differed significantly between the suppressive and conducive soils. Among dominant fungal operational taxonomic units (OTUs) affiliated to known genera, seventeen OTUs were detected exclusively in the suppressive soil. These OTUs were assigned to the Acremonium, Chaetomium, Cladosporium, Clonostachys, Fusarium, Ceratobasidium, Mortierella, Penicillium, Scytalidium, and Verticillium genera. Additionally, the relative abundance of specific members of the bacterial community was significantly higher in the suppressive and mixed soils than in the conducive soil. OTUs found more abundant in Fusarium wilt-suppressive soils were affiliated to the bacterial genera Adhaeribacter, Massilia, Microvirga, Rhizobium, Rhizobacter, Arthrobacter, Amycolatopsis, Rubrobacter, Paenibacillus, Stenotrophomonas, and Geobacter. Several of the fungal and bacterial genera detected exclusively or more abundantly in the Fusarium wilt-suppressive soil included genera known for their activity against F. oxysporum. Overall, this study supports the potential role of known fungal and bacterial genera in Fusarium wilt suppressive soils from Châteaurenard and pinpoints new bacterial and fungal genera for their putative role in Fusarium wilt suppressiveness.